Pengaruh Kompetensi, Kompensasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Pande Agung Segara Dewata - Sanjaya, I Kadek Edy; Indrawati, Ayu Desi (E-Jurnal Manajemen; Vol 3 No 1 (2014), 2014)
This research aims to know the influence of competencies, compensation, and work environment on performance of employees simultaneously or partially. This research takes the location of PT. Pande Agung Segara Dewata by using all employees as respondents research. Hypothesis testing in this study using multiple linear regression analysis. Analysis of the results obtained showed a simultaneous competencies, compensation, and work environment influence significantly to the performance of employees. In partial compensation, and competence, the work environment is also known a significant and positive impact on employee performance. Keywords: employee performance, competencies, compensation, and work environment